1995
DOI: 10.1152/ajpgi.1995.268.1.g161
|View full text |Cite
|
Sign up to set email alerts
|

The tachykinin receptors inducing contractile responses of canine ileum circular muscle

Abstract: This study sought to determine which tachykinin receptors were involved in contractile responses of circular muscle to tachykinins infused into isolated segments of canine ileum. Selective agonists for neurokinin receptors NK1 and NK2 as well as for substance P (SP) and neurokinin A (NKA) were infused, and selective antagonists against NK1, NK2, and NK3 receptors were tested. The responses to a submaximal concentration of NKA were reduced by a selective NK2 antagonist, SR-48968, and abolished by a combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…The present study, using an in vitro smooth muscle superfusion system (Coleman & Nials, 1989;Garcia-Villar et al, 1995), confirms the already well-documented stimulatory action of SP on intestinal contractility (Maggi et al, 1993c, for review;Suzuki et al, 1994;Daniel et al, 1995 (Al-Saffar et al, 1993;Rahman et al, 1994). shown that SP may influence intestinal secretion in mice by promoting the release of mast cell mediators (Wang et al, 1995).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The present study, using an in vitro smooth muscle superfusion system (Coleman & Nials, 1989;Garcia-Villar et al, 1995), confirms the already well-documented stimulatory action of SP on intestinal contractility (Maggi et al, 1993c, for review;Suzuki et al, 1994;Daniel et al, 1995 (Al-Saffar et al, 1993;Rahman et al, 1994). shown that SP may influence intestinal secretion in mice by promoting the release of mast cell mediators (Wang et al, 1995).…”
Section: Discussionsupporting
confidence: 85%
“…Histochemical, functional and kinins may alter motility, secretion, blood flow and even imradioligand binding studies have provided evidence for the mune functions in connection with gut inflammatory processes presence of these receptors in neural and non-neural structures (Sharkey, 1992;Otsuka & Yoshioka, 1993). SP has been suggested as a major contractile stimulatory transmitter of the non-adrenergic non-cholinergic (NANC) system controlling 'Author for correspondence at: INRA, Pharmacology and gastrointestinal motility (Nakanishi, 1991;Maggi et al, 1993b; Toxicology Unit, 180, Chemin de Tournefeuille, BP.3, 31931 Smits & Lefebvre, 1994 Pharmacology (1996Pharmacology ( ) 118, 1253Pharmacology ( -1261 genic effects, by interacting directly with both NK1 and NK2 receptors in the smooth muscle membrane, and indirectly via neurogenic atropine-sensitive pathways probably involving NK3 receptors (Maggi et al, 1993;Daniel et al, 1995;HolzerPetsche, 1995). Nevertheless, some studies have also reported SP-induced release of a putative NANC inhibitory transmitter, or inhibition of acetylcholine release, eventually leading to gastrointestinal smooth muscle relaxation (Fox & Daniel, 1986;Maggi et al, 1993b;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NK1 receptors are also implicated in the descending relaxant reflex responses and in ascending contraction [26] . NK1 and NK2 receptors are activated in the contractile responses induced by SP and NKA in canine ileum circular muscle [27] and mediate nonadrenergic, noncholinergic excitatory neurotransmission in hamster ileum [28] . In muscle cells of rat intestine, the coexistence of NK1, NK2, and NK3 tachykinin receptors has been described [29] .…”
Section: Effects Of Tachykinin Receptor Antagonistsmentioning
confidence: 99%
“…The tachykinin SP acts on neurokinin (NK) receptors that are present on mast cells (NK 1 receptors; Cooke et al 1998;Okada et al 1999), epithelial cells (NK 1 receptors; Southwell and Furness 2001), smooth muscle cells (NK 1 and NK 2 receptors), and enteric neurons (NK 1 and NK 3 receptors). In the small intestine of guinea pig, rat, dog, and human tachykinins have been described to exert a direct excitatory effect on the CM and LM by binding to NK 1 and/or NK 2 receptors (Bartho and Holzer 1985;Daniel et al 1995;Holzer and Holzer-Petsche 1997a, b;Lordal and Hellstrom 1999;Zagorodnyuk et al 1997).…”
Section: Substance P-and/or Enk-ir Myenteric Lm Motor Neuronsmentioning
confidence: 99%